Community-Based Exercise for Chronic Disease Management: An Italian Design for the United States?. (October 2014) - Weinrich, Michael; Stuart, Mary; Benvenuti, Francesco
Although only a small proportion of older adults in the United States engage in recommended amounts of physical exercise, the health benefits of exercise for this population and the potential for lowering health care costs are substantial. However, access to regular exercise programs for the frail elderly and individuals with disabilities remains limited. In the context of health reform and emerging opportunities in developing integrated systems of care, the experience in Tuscany in implementing a community-based program of exercise for the elderly should be of interest.